2020
DOI: 10.1080/02656736.2020.1750713
|View full text |Cite
|
Sign up to set email alerts
|

MR-guided microwave ablation in hepatic malignancies: clinical experiences from 50 procedures

Abstract: Purpose: To investigate technical success, technique efficacy, safety and outcome of MR-guided microwave ablation (MWA) in hepatic malignancies. Material and methods: In this prospective IRB-approved study, patients scheduled for percutaneous treatment of hepatic malignancies underwent MR-guided MWA in a closed-bore 1.5 T MR system. Technical success was assessed on post-procedural MR control imaging. Technique efficacy was evaluated 4 weeks after the procedure on multi-parametric MRI. Assessment of safety fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…However, due to insufficient MRI-compatible ablation equipment, complicated operation, prone to artifacts, and high cost, only a few medical centers specializing in MRI interventional treatment are performing MRI-guided ablations. [135][136][137] Improving the visibility of target tumors before ablation and enhancing the sensitivity in detecting residual tumorous tissue after ablation are challenges for the current image guidance techniques. Nevertheless, achieving complete ablation of target tumors has always been our main goal.…”
Section: Image Guidance Techniquesmentioning
confidence: 99%
“…However, due to insufficient MRI-compatible ablation equipment, complicated operation, prone to artifacts, and high cost, only a few medical centers specializing in MRI interventional treatment are performing MRI-guided ablations. [135][136][137] Improving the visibility of target tumors before ablation and enhancing the sensitivity in detecting residual tumorous tissue after ablation are challenges for the current image guidance techniques. Nevertheless, achieving complete ablation of target tumors has always been our main goal.…”
Section: Image Guidance Techniquesmentioning
confidence: 99%
“…Weiss et al [ 26 ] performed MWA on 50 patients under 1.5-T MR guidance and found that the median OS was 41.6 months, and only 4 patients (8%) had local recurrence after the procedure. Yang et al [ 27 ] enrolled 26 patients (38 lesions) in their study, and the primary efficacy rate of MWA was 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, MR-guided ablation has been gradually applied to the minimally invasive treatment of primary and metastatic renal malignancies [17,18]. The MR-guided method could ensure precise insertion of the applicator into the target tissue and enable monitoring and controlling the degree of tissue coagulation, to confirm that the tumor has been completely destroyed as well as reduce the impact on normal renal tissue and thermal damage to adjacent structures [19][20][21][22]. The characteristic of coagulative necrosis during MR-guided ablation is that the signal intensity on T2WI decreases while the signal intensity on T1WI increases.…”
Section: Discussionmentioning
confidence: 99%